Confidence regulates feedback processing during human probabilistic learning - Yehuda, MB; Murphy, RA; Le Pelley, ME; Navarro, DJ; Yeung, N (American Psychological Association, 2024)
Uncertainty presents a key challenge when learning how best to act to attain a desired outcome. People can report uncertainty in the form of confidence judgments, but how such judgments contribute to learning and subsequent decisions remains unclear. In a series of three experiments employing an operant learning task, we tested the hypothesis that confidence plays a central role in learning by regulating resource allocation to the seeking and processing of feedback. We predicted that, as participants’ confidence in their task knowledge grew, they would discount feedback when it was provided and be correspondingly less willing to pay for it when it was costly. Consistent with these predictions, we found that higher confidence was associated with reduced electrophysiological markers of feedback processing and decreased updating of beliefs following feedback receipt. Bayesian modeling suggests that this decrease in processing was due to a drop in the expected informative value of novel information when participants were highly confident. Thus, when choosing whether to pay a fee to receive further feedback, participants’ subjective confidence, rather than the objective accuracy of their decisions, guided their choices. Overall, our results suggest that confidence regulates learning and subsequent decision making.